COMPARATIVE EFFECTIVENESS OF MULTI ORAL ANTIDIABETIC DRUGS VERSUS INSULIN THERAPY FOR GLYCEMIC CONTROL IN TYPE 2 DIABETES MELLITUS - Pandit, Abha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Most antihyperglycemic drugs other than insulin reduce glycosylated hemoglobin (HbA1c) to similar levels but differ in respect to pathophysiological effects and safety. The decline in blood sugar control with oral anti-diabetic relates to many factors, as progressive loss of beta cell function, comorbidities, lifestyle factors, and glucotoxicity. The study objective was examination of safe, sustained reduction of HbA1c, by the modification of diabetes disease course, and averting complication. Insulin in real life practice with appropriate current oral drugs and supplementary insulin regimen. Methods: Herein, a comparative study spanning 6 months outdoor management of Type 2 diabetes patients on triple oral anti-diabetic drug regimen (26 patients) and on premix insulin regimen (34 patients) was undertaken at a tertiary care center in Central India. Results: The study reveals that addition of insulin in poorly controlled Type 2 diabetes patients on metformin and sulfonylurea treatment, achieve a higher reduction of HbA1c as well as fasting plasma glucose and postprandial glucose control than the three-drug combination therapy comprising metformin, sulfonylurea plus acarbose. However, there is only some increase in the risk of hypoglycemia. Conclusion: Premix insulin can be preferred in older, long disease bearing patients where too tight glycemic control is not envisaged, and shall be balanced safe and efficacious treatment. Keywords: Type 2 diabetes mellitus, Insulin therapy, Triple oral anti-diabetic therapy, Premix insulin.